Climate gentrification in coastal regions: planning and policy recommendations to mitigate displacement in marginalized Miami communities - Lewis, Alexandra (Kansas State University, 2023)
Anthropogenic disasters, which arise from human actions or errors over time, are intricately linked to global warming, resulting in alarming phenomena such as sea level rise, wildfires, and extreme temperature events at a global scale. The climate gap describes how the consequences related to climate change dramatically affect socially vulnerable communities greater than others, influencing their inability to effectively cope or recover from climate related disasters. The path of climate recovery involves reinvestment in aging infrastructure and revitalization of existing green space which often influences climate gentrification in historically disadvantaged areas. Climate gentrification is an unequivocal manifestation of climate change, wherein socioeconomic vulnerabilities are amplified, culminating in the displacement of those who lack the means to endure the demands of resiliency. Today, Miami exhibits clear equity gaps in resilience plans as a result of concentrated efforts to prioritize economic growth with limited strategies in place to safeguard affordable housing for disadvantaged communities facing the pressures of reinvestment. Since the beginning of the 20th century, low-income and minority residents were confined to live in the city’s urban core, now as the impacts of climate change are increasing, private developers are seeking to reinvest in the city center due to its elevation from the sea. In this report, I explore the social and economic impacts of resilient initiatives implemented in disadvantaged areas to provide recommendations encouraging the risk reduction of displacement through planning practices. Applying a justice framework assesses the city’s ability to achieve climate resilience in a fair and equitable manner. This analytical approach acknowledges the impact of culture, resources, and authority and reflects on Miami’s ability to pursue climate justice.
Keywords: Miami; Climate gentrification